Pulmonary Low Attenuation Areas on CT in ANCA-associated Vasculitis: A quantitative and semi-quantitative analysis correlated with pulmonary function testing for obstructive airway disease - Cox, Christian; Bartholmai, Brian; Baqir, Misbah; Geske, Jennifer; Ulrich, Specks (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Objective: A subset of ANCA-associated vasculitis (AAV) patients are known to manifest obstructive airway disease. Using low attenuation areas (LAA) in the lung on HRCT as an imaging marker for obstructive airway disease, we analyze HRCT studies in AAV patients compared to a matched non-AAV group using visual semi-quantitative and automated quantitative analysis for presence and severity of LAA. Furthermore, HRCT and pulmonary function testing are compared to assess agreement between tests for airway obstruction.Materials and Methods: 100 randomly selected AAV patients with HRCT were compared to 100 best-fit matched control subjects. HRCT cases were visually assessed for LAA, along with additional pulmonary patterns. Automated quantitative software analyzed images for texture features and volume of attenuation values of −950 HU or less (e-950). Evidence of obstructive airway disease established by pulmonary function testing, when available, was compared to HRCT analysis for LAA.  Additional clinical information, diagnostic testing and mortality data were also compared.Results: Both study groups were comprised of 57 females and 43 males with 35 smokers averaging 10.7 pk/yrs, with average age for the AAV and control groups being 59.4 yrs and 61.9 yrs, respectively. Visually, 46 AAV patients demonstrated LAA on HRCT compared to 25 control patients (p=0.0017) with the difference in LAA presence entirely within the non-smoking subgroup (25 to 3, respectively, p=